Coordination, organizations, institutions, and norms in agent systems IX : COIN 2013 International Workshops, COIN@AAMAS, St. Paul, MN, USA, May 6, 2013, COIN@PRIMA, Dunedin, New Zealand, December 3, 2013, Revised Selected Papers - Dignum, Frank; Riemsdijk, M. Birna; Chopra, Amit K.; Balke, Tina (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed proceedings of the 9th International Workshops on Coordination, Organizations, Institutions and Norms in Agent Systems, COIN 2013. The workshops were co-located with AAMAS 2013, held in St. Paul, MN, USA in May 2013, and with PRIMA 2013, held in Dunedin, New Zealand, in December 2013. The 18 full papers were carefully reviewed and selected from 28 submissions and are presented together with two invited papers. The papers are organized in topical sections such as coordination, organizations, institutions, norms, norm conflict, and norm-aware agents.